2015
DOI: 10.1016/j.gexplo.2015.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of bacterial leaching of antimony, chromium, copper, manganese, nickel, and zinc from contaminated sediment

Abstract: a b s t r a c tThere is an environmental risk of Sb becoming a major pollutant due to the quick increase in the production of Sb industry. However, there have been few investigations on interactions between Sb and microorganisms and bioremediation of Sb this paper presents an investigation on bioleaching of Sb from contaminated sediment which is collected in the vicinity of a Sb processing plant using the iron-oxidizer, Acidithiobacillus ferrooxidans. The bioleaching of Cr, Cu, Mn, Ni, and Zn in the sediment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…These results are in agreement with Nguyen et al (2015b), who reported 90 and 30 % of Mn and Zn solubilization, respectively, in a medium without nitrogen sources (experiments were carried out at 5 % of sediment and inoculated with Acidithiobacillus ferrooxidans).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…These results are in agreement with Nguyen et al (2015b), who reported 90 and 30 % of Mn and Zn solubilization, respectively, in a medium without nitrogen sources (experiments were carried out at 5 % of sediment and inoculated with Acidithiobacillus ferrooxidans).…”
Section: Resultssupporting
confidence: 93%
“…For all the media evaluated in this report with high pH and tailings concentrations, probably the removal of metals obtained was mainly influenced by chemical lixiviation catalyzed by Fe 2+ and biogenic H 2 SO 4 (reaction 2) (Nguyen et al 2015b).…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Vouillamoz and Milke, for example, have shown convincing evidence that rye grass is effective in removing mixed contaminants from soil (Vouillamoz and Mike, 2001). The most common contaminants found in mixed-contaminated soil (Cheng et al, 2008), such as co-contaminated river sediment are pyrene, phenanthrene, lead and zinc (Wang et al, 2014., Akcil et al, 2015;Nguyen et al, 2015). To date, studies on enhanced phytoremediation have not yet addressed the rhizosphere effect on mixed contaminants (Priha et al, 1999).…”
Section: Introductionmentioning
confidence: 99%